Theory and system research of communication with tracking and pointing function for hunter robot - YU Yang1; MIN Fu-hong2; NI Xiao-wu1; ZHANG Hong-chao1 (Tongxin xuebao)
Eye-hole wave communication frame was proposed first time.Tracking and pointing model of communication was put forward.New era of short distance optical communication was pioneered.Acguisition method of beaconing light was researched and acquisition time was computed.Two dimension pointing error normal distribution and rayleigh dis-tribution were simulated.Dithering Rician distribution of target pointing was simulated.Attenuation losing formula of receiving len’ diaphragm detection was calculated and simulated.Three dimension pointing error normal distribution and rayleigh distribution were proposed.Three dimension rayleigh fold dithering distribution was proposed.Simulation re-sults are computed and the results is shown.The concept of eye-hole wave communication is proposed first time.The two dimension and three dimension theory model of tracking/pointing dithering problem of robot are put forward and attenua-tion model is presented also.